Chronic bilateral dislocation of temporomandibular joint - Shakya, S; Ongole, R; Sumanth, KN; Denny, CE (Kathmandu University Medical Journal, 2010)
Dislocation of the condyle of the mandible is a common condition that may occur in an acute or chronic form. It is characterised by inability to close the mouth with or without pain. Dislocation has to be differentiated from subluxation which is a self reducible condition. Dislocation can occur in any direction with anterior dislocation being the commonest one. Various predisposing factors have been associated with dislocation like muscle fatigue and spasm, the defect in the bony surface like shallow articular eminence, and laxity of the capsular ligament. People with defect in collagen synthesis like Ehler Danlos syndrome, Marfan syndrome are said to be genetically predisposed to this condition. Various treatment modalities have been used ranging from conservative techniques to surgical methods. Acute dislocations can be reduced manually or with conservative approach and recurrent and chronic cases can be reduced by surgical intervention. Though the dislocation in our case was 4 months a simple manual reduction proved to be successful. We believe that manual reduction can be attempted as first line of treatment prior to surgical intervention. Key words: Temporomandibular joint; Dislocation; Management DOI: 10.3126/kumj.v8i2.3570 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 251-256